2023
DOI: 10.3390/ph16020134
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Rhythmologic Effects of Push-Dose Landiolol in Critical Care—A Retrospective Cross-Sectional Study

Abstract: Background: The highly β1-selective beta-blocker Landiolol is known to facilitate efficient and safe rate control in non-compensatory tachycardia or dysrhythmia when administered continuously. However, efficacy and safety data of the also-available bolus formulation in critically ill patients are scarce. Methods: We conducted a retrospective cross-sectional study on a real-life cohort of critical care patients, who had been treated with push-dose Landiolol due to sudden-onset non-compensatory supraventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…In this study, we were able to show that prior administration of oral β-blockers had no significant impact on rate or rhythm control after Landiolol bolus administration ( Figure 2 sums up the study findings). As already described in our initial cross-sectional study [ 17 ], Landiolol appears to have a high potential for successful rate and rhythm control in critically ill patients with a sudden onset of tachyarrhythmia (rate control in 11 and rhythm control in 9 patients). However, in one-third of patients, there was no effect.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, we were able to show that prior administration of oral β-blockers had no significant impact on rate or rhythm control after Landiolol bolus administration ( Figure 2 sums up the study findings). As already described in our initial cross-sectional study [ 17 ], Landiolol appears to have a high potential for successful rate and rhythm control in critically ill patients with a sudden onset of tachyarrhythmia (rate control in 11 and rhythm control in 9 patients). However, in one-third of patients, there was no effect.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, we were able to show that prior administration of oral β-blockers had no significant impact on rate or rhythm control after Landiolol bolus administration (Figure 2 sums up the study findings). As already described in our initial cross-sectional study [17],…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, compelling evidence suggests that inflammation and oxidative stress play significant roles in the development of AF [ 78 ]. Landiolol showed a protective effect on LPS-induced systemic inflammation model in an animal study, being associated with a decrease in high mobility group box-1 protein (HMGB-1) and decreasing IL-6 levels, while inhibiting TNF-alpha levels [ 78 , 79 ]. The animal model demonstrated that landiolol’s anti-inflammatory effect extends to the inhibition of the inflammatory and vasoconstrictor peptide endothelin (ET) 1 [ 80 ].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%